(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The article discusses interactive methods and their application in the latest technologies in teaching physics and astronomy, and also discusses the main advantages associated with the educational process